2(x+2)(x-4)4=0

Simple and best practice solution for 2(x+2)(x-4)4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+2)(x-4)4=0 equation:


Simplifying
2(x + 2)(x + -4) * 4 = 0

Reorder the terms:
2(2 + x)(x + -4) * 4 = 0

Reorder the terms:
2(2 + x)(-4 + x) * 4 = 0

Reorder the terms for easier multiplication:
2 * 4(2 + x)(-4 + x) = 0

Multiply 2 * 4
8(2 + x)(-4 + x) = 0

Multiply (2 + x) * (-4 + x)
8(2(-4 + x) + x(-4 + x)) = 0
8((-4 * 2 + x * 2) + x(-4 + x)) = 0
8((-8 + 2x) + x(-4 + x)) = 0
8(-8 + 2x + (-4 * x + x * x)) = 0
8(-8 + 2x + (-4x + x2)) = 0

Combine like terms: 2x + -4x = -2x
8(-8 + -2x + x2) = 0
(-8 * 8 + -2x * 8 + x2 * 8) = 0
(-64 + -16x + 8x2) = 0

Solving
-64 + -16x + 8x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '8'.
8(-8 + -2x + x2) = 0

Factor a trinomial.
8((-2 + -1x)(4 + -1x)) = 0

Ignore the factor 8.

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {-2, 4}

See similar equations:

| -34=42+-4v | | (X+3)(X+4)(X+5)=0 | | (X-3)(Y+7)=0 | | 6(5-2y)-5(y+3)= | | 5x-(x-18)=6-2(x+15) | | x*(x+1)(x+2)(x+3)=0.5625 | | 4(2+3)-2y= | | X^3-3x^2+x+1=0 | | -16-8(2a+3)=23-2a | | 4(2+3)-2y=3(4y+3) | | -14x^3+9x^2-2=0 | | 3/2x=189/20 | | -19x+4=0 | | 2(4w-1)=-10(w-3)+4 | | 5(x+5)=27 | | 30-5x=-5 | | 3.14*x^5-6x^4-9=0 | | pi*x^5-6x^4-9=0 | | 5x+5=137-6x | | 6x=121-5x | | 4x=63-5x | | 9(m-3)+3m=7m+43 | | 3.14x^5-6x^4-9=0 | | 12x-2=7x+23 | | 12x-2=7x+32 | | y=40ln(3x+8) | | 12-2u=8u+45 | | 124-3x=24+19 | | x/4+x+5/3=4 | | x-1/2x+x+3/4x=5/8 | | X^3-3x^2-x-3=0 | | 5/x+6=17/x |

Equations solver categories